Confinement-concrete interaction in pre-tensioned partial steel-confined concrete. (February 2020) - Chin, Chee-Loong; Ong, Chin-Boon; Tan, Jia-Yang; Ma, Chau-Khun; Awang, Abdullah Zawawi; Omar, Wahid
Abstract: External confinement is an attraction technique to enhance strength and deformability of high strength concrete. Previous research revealed that pre-tensioned confinement is an approach to improve existing confinement techniques. However, limited experimental data are available especially for pre-tensioned steel-confined high strength concrete in square section. On the other hand, the stress distribution in confined square section and partial confinement is not clearly understood. This paper explores the compressive behaviour of pre-tensioned steel-confined high strength concrete. A new confinement-concrete interaction based on localised force and stress distribution in circular and square partial confined concrete is presented. By incorporating the confinement-concrete interaction, failure surface of confined concrete is calibrated with an experimental database. Confinement effect is then estimated based on the calibrated failure surface. This approach is shown to be more accurate than existing confinement models.